DEVELOPMENT OF GROUP TACTICAL ACTIONS IN ATTACK AND DEFENSE IN HANDBALL (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study examines the content, significance, and methods of developing group tactical actions performed during attacking and defensive phases in the sport of handball. The research focuses on issues such as players’ mutual cooperation, coordination of movements, rapid decision-making, and increasing the effectiveness of team tactics. In addition, methodological recommendations aimed at improving group tactical actions during the training process are presented. This topic is of great importance for enhancing players’ game performance and achieving high results in competitions.